1986
DOI: 10.1029/jd091id12p13137
|View full text |Cite
|
Sign up to set email alerts
|

Results from the balloon ozone intercomparison campaign (BOIC)

Abstract: The purpose of the Balloon Ozone Intercomparison Campaign (BOIC) was to assess the accuracy and precision of various ozone measurement systems under development and those flown operationally. Ozone observations made by in situ UV absorption photometers from four groups, two solar UV absorption photometers, three varieties of electrochemical sondes, and a mass spectrometer were intercompared in three flight missions, each involving several balloon flights. Concurrent Umkehr and satellite observations were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 114 publications
(63 citation statements)
references
References 20 publications
5
54
0
1
Order By: Relevance
“…The NASA JSC UV photometer used in BIC was compared with five other UV photometers during the Balloon Ozone Intercomparison Campaign (BOIC) [Hilsenrath, et al (1985); Hilsenrath et al (1986)]. …”
Section: The In-situ Ultraviolet Absorption Photometermentioning
confidence: 99%
See 2 more Smart Citations
“…The NASA JSC UV photometer used in BIC was compared with five other UV photometers during the Balloon Ozone Intercomparison Campaign (BOIC) [Hilsenrath, et al (1985); Hilsenrath et al (1986)]. …”
Section: The In-situ Ultraviolet Absorption Photometermentioning
confidence: 99%
“…Random and systematic errors (95% confidence level) in the cross section at 254 nm are estimated to be 6% (R. D. Hudson, personal communication, 1986). Mauersberger et al (1986) recently measured the cross section of ozone at 254 nm with a 95% confidence level uncertainty of 1.2%. The more conservative uncertainty of Hudson is used here.…”
Section: [0 3] ~ F[m]mentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to the Brewer-Milford type of electrochemical ozone sensor [13]. Various studies using a standard UV photometer have shown that concentrations of tropospheric ozone are overestimated with ECC sondes, but underestimated by Brewer Mast Sondes [16][17][18][19][20]. The two error sources mainly affecting the tropospheric part of the profile are the contamination of the sonde sensor with reducing agents (SO 2 and NO x ), causing a negative bias especially for Brewer Mast sondes, and the estimation of the background current, causing presumably a positive bias for ECC sondes and a negative bias for Brewer Mast sondes [21].…”
Section: Ballonborne Ozonesondementioning
confidence: 94%
“…Applying the full background current correction leads to an underestimation in stratospheric ozone of amount 2-6 % [9], possibly indicating a need to separate corrections for tropospheric and stratospheric data. Intercomparisons in 1970Intercomparisons in , 1978Intercomparisons in and 1984 had shown that ECC sondes measured more ozone in the mid-troposphere than BM sondes by about 15-20 % (with a range of 7-8 %); in the stratosphere, BM sondes gave more ozone than ECC sondes, usually by less than 5 % [4,5,17]. An intercomparison in 1991 gave opposite results [8].…”
Section: Ballonborne Ozonesondementioning
confidence: 96%